Digital Pricing A Guide to Strategic Pricing for the Digital Economy - Frohmann, Frank (Cham : Springer International Publishing : Imprint: Springer, 2023)
This is one of the first books to combine the current megatrend of digitalization and pricing as the most effective lever for increasing and sustaining profits. The book presents the basics of digital pricing as well as modeling methods and implementation examples. This structure helps in tackling the latest developments and challenges due to digitalization. Readers will gain a detailed insight into using innovative revenue and price models to generate a sustainable competitive advantage for their companies. The author uses his cross-industry experience to draw on several examples of innovative digital pricing approaches which can be applied in industrial sectors such as automotive, industrial goods and machinery, as well as service sectors like telecommunications, transportation and tourism.
Basics of Price Management -- Characteristics of Digital Pricing -- Business Models -- Revenue Models -- Pricing Process Part 1: Analysis -- Pricing Process Part 2: Strategy -- Pricing Process Part 3: Structure (3a: Price Differentiation) -- Pricing Process Part 3: Structure (3b: Price Models) -- Pricing Process Part 3: Structure (3c: Price Optimization) -- Pricing Process Part 3: Structure (3d: Portfolio Pricing) -- Pricing Process Part 4: Implementation -- Pricing Process Part 5: Monitoring -- Pricing Process and Pricing Psychology. .
Keywords: Marketing; Business information services; Management; Sales management; Marketing; IT in Business; IT in Business; Management; Sales and Distribution